Gilles Deleuze and Film Criticism Philosophy, Theory, and the Individual Film - Lash, Dominic; Law, Hoi Lun. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"Gilles Deleuze and Film Criticism is a remarkable collection undertaking with spirit and intelligence to grapple with what Trevor Mowchun calls the 'spates' of criticism in the writings of one of the most challenging thinkers on film. Every one of the individual forays adeptly demonstrates the value of combining film analysis with attentive meta-critical commentary and conceptual elucidation of Deleuze's terms and tendencies. Aside from the inherent interest of the essays themselves, this volume's major contribution to film studies lies in its potential to re-energise debate on a vital issue for the discipline: namely, the relation between theory and criticism." --Alex Clayton, Associate Professor in Film and Television, University of Bristol, UK This book is the first collection of essays to offer detailed examinations of the role that close attention to individual films plays in the philosopher Gilles Deleuze's work on cinema. In the last two decades, Deleuze's two books on film have had an enormous influence on Film Studies, profoundly affecting thinking about movement, time, history, and other topics. Theoretically ambitious and philosophically rich but clearly written by a broad range of established and emerging international film scholars, the chapters in this volume will both contribute to, and in places challenge, the vibrant field of Deleuzian film studies. Topics covered range from the relationship of Deleuze to film criticism; the role of theories of movement; and studies of works by major filmmakers including Federico Fellini, Werner Herzog, Vincente Minnelli, and Orson Welles. This book will be of interest not only to specialists in Deleuze but to anybody engaged with the close study of film and its philosophical ramifications. Dominic Lash is the author of The Cinema of Disorientation: Inviting Confusions (2020) and Robert Pippin and Film: Politics, Ethics, and Psychology after Modernism (2022). He has taught film at many institutions, including the universities of Bristol and Oxford, and has published in journals such as Screen; Movie: A Journal of Film Criticism; Film and Philosophy; and Film-Philosophy. Hoi Lun Law is Teaching Fellow in Film Studies at the University of Edinburgh, UK. He is the author of Ambiguity and Film Criticism: Reasonable Doubt (2021).
1. Introduction -- 2. Part 1: Perspectives on Method -- 2. What does Deleuze do when he does film criticism? -- 3. Deleuze and the film in his Mind -- Part 2: Criticism, Philosophy, Theory -- 4. Gilles Deleuze and the Company of Critics: On Kubrick, Time, and Cinema -- 5. "Very Slight Differences": Deleuze and the Aesthetics of Cinematic Motion -- 6. . "Something Possible, Otherwise I Will Suffocate": A Marginal Reading of Chapter 7, Section 2 of Deleuze's The Time-Image -- Part 3: Films and Filmmakers -- 7. Banish All the World: Deleuze on Chimes at Midnight -- 8. Donen and Minnelli: An Exchange of Energies -- 9. Deleuze and Fellini: And the Ship Sails On. 10. Hypnosis-images: indiscernibility and hypnotic agency in Gilles Deleuze's Heart of Glass.
Keywords: Motion pictures -- Aesthetics; Aesthetics; Motion pictures; Film Philosophy; Aesthetics; Film Theory